Antenatal interpersonal sensitivity as an early predictor of vulnerable mother–infant relationship quality. (October 2019) - Raine, Karen Hazell; Boyce, Philip; Thorpe, Karen
Maternal mental health problems in the perinatal period incur significant human and economic costs attributable to adverse child outcomes. In response, governments invest in screening for perinatal depressive symptoms. Mother–infant relationship quality (MIRQ) is a key mechanism linking maternal perinatal mental health to child outcomes. Perinatal depressive symptoms are typically transient while personality style, including interpersonal sensitivity, is a more stable construct. We have demonstrated that antenatal interpersonal sensitivity independently predicted MIRQ at 12 months postpartum. Building on our previous work, the objective of this study was to examine the associations of antenatal interpersonal sensitivity and depressive symptoms with MIRQ 1 year postnatal. A sample of 73 women attending routine antenatal care, 61 (84%) from ethnically diverse populations, were studied across the perinatal period. At ⩽26 weeks, gestation interpersonal sensitivity and depressive symptoms were measured. At 12 months, postnatal mental health and MIRQ was assessed in 35 of the mother–infant dyads. We found no significant statistical association between antenatal interpersonal sensitivity and depressive symptoms with postnatal MIRQ. Interpersonal sensitivity ( r  = –.24) showed weak association with MIRQ. Depressive symptom scores were not associated ( r  =–.01). Maternal sensitivity assessment (MIRQ) using the CARE-Index identified low mean scores signifying low levels of maternal sensitivity (potential range 0–14; mean score = 6.3). We cautiously suggest that the findings raise questions about the presentation and assessment of perinatal mental health status among ethnically diverse populations and scoping of parenting support needs within this population.